2016
DOI: 10.1021/acs.jpca.5b11869
|View full text |Cite
|
Sign up to set email alerts
|

Dehydrohalogenation and Dehydration Reactions of i-C3H7Br and i-C3H7OH by Sodium Ions Studied by Guided Ion Beam Techniques and Quantum Chemical Methods

Abstract: Dehydrohalogenation and dehydration reactions of gas-phase i-C3H7Br and i-C3H7OH molecules induced by collision with Na(+), all participants being in their electronic ground state, were studied experimentally in our laboratory using a radiofrequency-guided ion beam apparatus and covering the 0.10-10.00 eV center of mass (CM) energy range. In Na(+) + i-C3H7Br collisions the formation of [C3H6-Na](+) and [HBr-Na](+) by dehydrohalogenation was observed and quantified, as well as that of the ion-molecule adduct [N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 37 publications
(63 reference statements)
0
5
0
2
Order By: Relevance
“…In fact, at 4 and 6 eV nominal CE the ion-molecule collision complex can successfully overcome the barrier separating adduct (1) and T1 structures. In previous studies on reactive ionmolecule processes involving non-covalent adducts 58,59 , it was found that their formation was relevant only at low energies. Hence, for nominal CEs higher than the potential energy barrier associated to P1 structure formation, non-covalent adduct contribution ought to be regarded as negligible, so that only P1 is expected to contribute to the measured signal at m/z 135.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, at 4 and 6 eV nominal CE the ion-molecule collision complex can successfully overcome the barrier separating adduct (1) and T1 structures. In previous studies on reactive ionmolecule processes involving non-covalent adducts 58,59 , it was found that their formation was relevant only at low energies. Hence, for nominal CEs higher than the potential energy barrier associated to P1 structure formation, non-covalent adduct contribution ought to be regarded as negligible, so that only P1 is expected to contribute to the measured signal at m/z 135.…”
Section: Discussionmentioning
confidence: 99%
“…In Na + + i-C 3 H 7 OH, the exothermic character of reactions (1) and (2) is smaller than in the case of the lithium ion, with the latter being faster at some 9.6 × 10 9 cm 3 s 1 molec 1 , while is proved impossible to measure the excitation function for the more endothermic reaction (1) experimentally. 50 For this system the transition state potential energy barrier increases. For K + + i-C 3 H 7 OH, reaction (1) is endothermic, while (2) is exothermic but the transition state potential energy barrier is so much higher than the asymptotic one of both reactions that it was not possible to measure their excitation functions.…”
Section: Bmentioning
confidence: 92%
“…For M + + i-C 3 H 7 Br, the reaction endothermicity increases from lithium to potassium ions, being reaction cross sections for Li + and Na + in the range of a few Å 2 (although something larger in the case of Na + ) 50 while those for K + are in the tenths Å 2 range. 22 For M + + i-C 3 H 7 OH a similar behavior is also found, showing large cross section values in collisions with Li + and Na + (in the high 10 Å 2 range for the former and of a few 10 2 Å 2 range for the latter) while for K + , cross section values are in the 10 2 Å 2 range.…”
Section: Bmentioning
confidence: 98%
See 2 more Smart Citations